La casa como espacio de disociación y represión familiar. A propósito de la obra homónima de Daniel Gallegos - Alvarado Vega, Óscar Gerardo (2013)
In the Literary work La casa from Daniel Gallegos, the home, if it can be called that, becomes a place that imprisonsits inhabitants, because rather than a space to allow the harmony of living, it becomes or is transformed into alabyrinth or confinement, which gives everyone, and where on Teresa and her mother’s part, weaves a dimensionof selfishness, a desire to possess the House, without realizing that it is they who are possessed by the house. Theresult is family disintegration and the emergence or appearance of a space which makes coexistence now impossiblebecause the structure ends up separating the so-called family Group.